Sustainable Use of Greek Herbs By-Products, as an Alternative Source of Biologically Active Ingredients for Innovative Products - Dina, Evanthia; Vontzalidou, Argyro; Cheilari, Antigoni; Bagatzounis, Panagiotis; Agapidou, Eftyxia; Giannenas, Ilias; Grigoriadou, Katerina; Aligiannis, Nektarios (Frontiers in Nutrition, 2022)
The processing of Greek Medicinal & Aromatic Plants (MAPs) results in the production of a significant amount of plant by-products; herbal material of inferior quality and / or unusable plant parts, which are not commercially exploitable. An extensive study of Greek native species was performed, towards the production of innovative bioactive products using as raw materials the by-products obtained from the processing of cultivated MAPs. Origanum vulgare subsp. hirtum (oregano), Sideritis scardica (Greek mountain tea), Thymus vulgaris (thyme) and Matricaria recutita (chamomile) were selected due to their wide use for the preparation of beverages and culinary purposes. For the determination of the percentage of wastes, species were cultivated, dried and during processing, samples of different LOTs were measured, according to ISO 948:1980 Spices and condiments – Sampling method, in three years period (2018-2020). Results showed that “wastes” derived from the above mentioned species’ processing constitute 64%, 54%, 37%, and 24% of the total processed mass for thyme, oregano, mountain tea, and chamomile, respectively. In order to value the by-products as a potent source of bioactive ingredients, hydroalcoholic extracts of superior and inferior quality herbal material of the aforementioned plant species were produced and were chemically investigated using HPTLC and LC/MS techniques. Their antioxidant activity and total phenolic content (TPC) were also estimated. Based on the results, herbs’ by-products revealed similar chemical content to the superior herbal material, and strong antioxidant capacity related to a high phenolic content was detected in the case of Origanum vulgare subsp. hirtum, Thymus vulgaris and Sideritis scardica. Moreover, GC-MS analyses of essential oils of Origanum vulgare subsp. hirtum and Thymus vulgaris by-products, revealed the presence of carvacrol, thymol, γ-terpinene and p-cymene among the major constituents, underlying their potent use in the preparation of high added-value products such as enriched aromatic olive oils. Finally, LC-MS analyses of aqueous extracts of Sideritis scardica and Matricaria recutita by-products led to the identification of several bioactive compounds such as flavonoids and phenylpropanoids highlighting their potent exploitation for the production of innovative herbal teas such as instant beverages.